Growth performance, haematology and histopathology of African catfish (Clarias gariepinus) fed varying levels of Aloe barbadensis leaves - Adegbesan, Sherifat Ibidunni; Obasa, Samuel Olubodun; Abdulraheem, Ikililu (Journal of Fisheries, 2018)
One hundred and twenty Clarias gariepinus fingerlings (2.33 ± 0.07 g) were fed with 40% crude protein diets containing three concentrations of Aloe barbadensis leaves-paste: ABL1, 1%; ABL2, 2%; ABL3, 3%, and control, 0% ad libitum twice daily for 12 weeks. Mean weight gain and percentage weight gain increased (P < 0.05) as concentration of A. barbadensis increased. Survival rate decreased as concentration of paste increased. Differences (P < 0.05) seen in packed cell volume (PCV), haemoglobin (Hb), and red blood cell (RBC), thus highest in ABL3: PCV (36.67 ± 0.89%), Hb (12.37 ± 0.37 g dl–1) and RBC (3.47 ± 0.08×106 L–1) and lowest in control: PCV (22.0 ± 0.58%), Hb (7.37 ± 0.20 g dl–1) and RBC (2.07 ± 0.06 ×106 L–1). Liver histology of control fish was normal, while fatty degenerations were seen in the treated fish. The histology of fish kidney was normal in all treatments. The study concluded that 1% A. barbadensis leaves-paste could effectively improve growth performance, nutrient utilization and survival of cultured C. gariepinus.